Left ventricular filling and left bundle branch block: an echocardiographic and radionuclide study - Duriez, P; Assoun, B; Bussy, E; de Bourayne, J; Monségu, J; Ollivier, J P (Archives des maladies du coeur et des vaisseaux, 1992)
Left bundle branch block changes the activation and haemodynamics of the left ventricle. In order to evaluate its consequences on left ventricular filling, the duration of the isovolumic relaxation period, the velocities and the integrals of the rapid and slow filling waves were recorded by Doppler echocardiography and the ejection fraction, the peak filling rate and its time of apparition were measured by gamma angiocardiography in 18 patients aged 55 +/- 9 years and 18 control subjects aged 53 +/- 9 years. Left bundle branch block was associated with a prolonged isovolumic relaxation period (104 +/- 14 vs 88 +/- 11 ms) a delayed and reduced peak filling rate and an increased atrial filling velocity at a heart rate comparable to that of control subjects (69 +/- 9 vs 72 +/- 8 beats/mn). Despite these changes in left ventricular relaxation and filling and a reduced ejection fraction (55 +/- 7 vs 61 +/- 6%, p < 0.01) cardiac output was not significantly decreased in left bundle branch block (4.9 +/- 1 vs 5.2 +/- 0.9 l/mn). Therefore, left bundle branch block interferes with left ventricular filling and ejection fraction without decreasing the resting enddiastolic volume.